Combined analysis of differentially expressed lncRNAs and miRNAs in liver tissues of high-fat fed rabbits by transcriptome sequencing - Wang, Jie; Wang, Meigui; Shao, Jiahao; Liu, Zheliang; Fu, Chong; Chen, Guanhe; Zhao, Kaisen; Li, Hong; Sun, Wenqiang; Jia, Xianbo; Chen, Shiyi; Lai, Songjia (Frontiers in Genetics, 2022)
High-fat diet could lead to a series of metabolic diseases, including obesity, and its mechanism is not clear. In this study, the rabbit individuals were fed with high-fat diet, the liver tissues were collected, high-throughput sequencing technology was used to reveal the expression of lncRNA and miRNA difference, and the molecular regulation mechanism of lncRNA-miRNA. A total of 24615 DE lncRNAs and 52 DE miRNAs were identified, including 15 novel discovered DE miRNAs (5 up-regulated and 10 down-regulated). GO and KEGG analyzed 757139 target genes respectively, enriching the pathways related to lipid metabolism, including mucin O-glycan biosynthesis pathway, insulin resistance and glucagon signaling pathway. Moreover, 78 targeting relationships were obtained. Among them, miR-375-5p/LOC108175519, miR-181d-3p/LOC108178671, miR-450a-5p/LOC108176670, miR-135a-3p/LOC10817690, miR-450a-3p/LOC103345690 were proposed the first time. Significantly, miR-450a-5p/LOC108176670 and miR-135a-3p/LOC10817690 were related to lipid metabolism in the liver. This study provides a new idea for the study of steatosis caused by high-fat and a new perspective for gene therapy.